External negative pressure transiently reduces intravenous pressure and augments the arteriovenous pressure gradient in the affected limb segment. - Nigel A Callender; Lars Øivind Høiseth; Jonny Hisdal (PLoS ONE)
Recently intermittent negative pressure has emerged as a potential treatment in vascular disease and has similarities with established experimental interventions such as lower body negative pressure. The direct, local influences of either method upon intravascular pressure still require some clarification however, particularly in the immediate moments following onset. We investigated the acute intravascular pressure responses to intermittent cycles of negative pressure in the supine and sitting postures. Fifteen participants (6 female) received intermittent negative pressure cycles (-37 mmHg; 9.5-sec on, 7.5-sec off) upon the lower leg in both postures. Saphenous venous (n = 15), and dorsalis pedis artery pressure (n = 3) were recorded via pressure catheter, alongside beat-by-beat systemic cardiovascular parameters (heart rate and blood pressure; n = 15), from which the arteriovenous pressure gradient was ultimately derived. Negative pressure induced a transient reduction in local intravenous pressure (Supine: 14±3 mmHg to -18±6 mmHg, p<0.001; Sitting: 58±10 mmHg to 41±10 mmHg, p<0.001). Rate of venous pressure recovery during the negative pressure plateau phase was faster during sitting, than supine (1.94±0.72 vs. 1.06±0.69 mmHg·sec-1; p = 0.002). Local intraarterial pressure did not change. External negative pressure readily transmits to the superficial intravenous environment of the leg and transiently augments the arteriovenous pressure gradient. The greatest and most sustained effect was during the supine position. The augmented arteriovenous gradient might briefly produce Poiseuille-dependent haemodynamics before local autoregulatory mechanisms engage. These findings benefit understanding of the immediate in-vivo effects of negative pressure upon the local vasculature, and may partly account for the positive clinical effects of intermittent negative pressure treatments in vascular disease.